Look Inside a Tree - Richard Spilsbury (Oxford, United Kingdom Capstone Global Library Ltd, 2013)
Look inside a tree and discover a world of inhabitants! A close look at this microhabitat reveals an unbelievable variety of organisms. Vibrant photographs and detailed illustrations combine to make these books informative and engaging. A visual table of contents helps readers navigate the text, and informative labels make the photographs valuable sources of information.
Keywords: Endangered Species; PY-UOI - How the World Works